Naldinijeva Corografia ecclesiastica - kronika koprske škofije ali lokalna zgodovina? - Pobežin, Gregor (Clotho, 2024)
The Bishop of Koper Paolo Naldini, who took office in 1686, published the work Corografia ecclesiastica o sia descrittione della citta e della diocesi di Giustinopoli detto volgarmente Capo d’Istria (Ecclesiastic Local History or Description of the City and Diocese of Justinopolis, popularly Koper) in Venice in 1700. It is one of the most comprehensive studies of the area of the Koper Diocese. The work, which runs to just over 500 pages, is not the only local history of Istria, but it is particularly remarkable in the sense that it has a very clear central theme: the role and history of the Church in northern Istria, more specifically within the boundaries of the Diocese of Koper. Within the scope of his work, Naldini has drawn up a testament of great erudition. He was able to argue with other authors who had touched on the area of northern Istria, critically comparing individual testimonies from older local histories; he had a good overview of non-literary sources, and he also carefully collected epigraphic documents. A question that has not yet been asked, however, is whether Naldini’s local history is a historical work (in the strict sense of the word) or a chronicle. The answer is not easy, because the Corografia Ecclesiastica is a mix of different literary strategies, so that one is initially tempted to label the work as simply a survey of local history authored by a polymath. Nevertheless, it cannot be overlooked that in the most original passages, the principle of treatment of the material is distinctly chronicle-like.
Keywords: anali; annals; Cerkveni krajepis; chronicle; Corografia Ecclesiastica; Corografia ecclesiastica o sia descrittione della citta e della diocesi di Giustinopoli detto volgarmente Capo d’Istria; historiography; kronika; Naldini, Paolo; zgodovinopisje